Pengelolaan Sampah dalam Sektor Pariwisata Bali melalui Perspektif Administrasi Publik - Ni Putu Tirka Widanti; I Kadek Pageh Artha Widianta Putra (Lembaga Pengembangan Kinerja Dosen, 2026)
Tourism is a leading sector in Bali Province that significantly contributes to the regional economy. However, rapid tourism growth has also generated environmental problems, particularly the increasing volume of waste in tourist areas. This study aims to examine waste management in Bali’s tourism sector from the perspective of Public Administration. The research method employed is a literature review by analyzing five academic journals related to waste issues and sustainable tourism. The findings indicate that waste problems in Bali are caused not only by high tourist activities but also by weak policy implementation, poor inter-institutional coordination, and low community participation. From a public administration perspective, waste management requires the government’s role as policy maker, regulator, and effective public service provider. The application of good governance principles, multi-stakeholder collaboration, and institutional capacity building are essential in achieving sustainable tourism in Bali. This study emphasizes that waste management is a crucial component of tourism governance that must be integrated into regional public policies.